Efeito de sinigrina aplicada em folhas de brássicas sobre características biológicos de Plutella xylostella (L.) (Lepidoptera: Plutellidae) - Da Silva Carvalho, Jackeline [UNESP]; De Bortoli, Sergio Antonio [UNESP]; Thuler, Robson Thomaz [UNESP]; Goulart, Roberto Marchi [UNESP]; Volpe, Haroldo Xavier Linhares [UNESP] (Universidade Estadual de Maringa, 2010)
The objective of this work was to evaluate the effect of sinigrin applied to cabbage and broccoli leaves of biological aspects of Plutella xylostella. Two brassica cultivars, cabbage Da Georgia and broccoli Ramoso Piracicaba Precoce, were used and were treated with the following sinigrin solutions: 0.2, 0.4, 0.8, 1.6 and 3.2 mg mL-1 in solution 5% of Tween 20® and a control with Tween solution. Duration and viability of larval and pupal periods, pupal weight, longevity and sex ratio, female fertility, incubation period and egg viability were evaluated. The corrected reproductive potential index (PRC) was also calculated. The means were analyzed by the multivariate analysis of grouping and of main components. The PRC treatments presented 0.2 mg mL-1 in cabbage with larger reproductive potential. The multivariate analysis provided discrimination of treatments regarding the smaller tested concentration. By the results it is possible to conclude that low concentrations of sinigrin, in cabbage and broccoli, allow better development for P. xylostella.
Effect of sinigrin applied on brassics leaves on biological aspects of Plutella xylostella (L.) (Lepidoptera: Plutellidae)
Keywords: Broccoli; Cabbage; Diamondback moth; Glucosinolates; Reproductive potential